A closer look at opportunities for blind adults: Impacts of stigmatization and ocularcentrism. (September 2020) - Bulk, Laura Yvonne; Smith, Andrea; Nimmon, Laura; Jarus, Tal
Blind Canadians experience higher rates of unemployment, social isolation, and poverty than sighted Canadians. Examining what influences opportunities can help to identify the factors that disable blind people. During initial analysis, stigma and ocularcentrism emerged as important factors. Thus, this article examines how stigma operates culturally, socially, politically, and economically to shape opportunities among blind adults. Data were collected through in-depth, semi-structured interviews with six legally blind participants (visual acuity of 20/200 or below), aged 19–65 years. Thematic analysis was employed to understand the common and diverging narratives of participants. Within participant narratives, ocularcentrism is found to contribute to stigmatization at societal, interpersonal, and internalized levels. Opportunities are experienced within this context, and the stigmatization experienced both shaped and was shaped by participation in activities. It is imperative that a closer look is given to how stigma shapes the opportunities for blind people, so that individuals, teachers, practitioners, and policy makers can develop relevant and effective interventions and can challenge stigmatization.